Morphological types of spermatheca in Coreidae: bearing on intra-familial classification and tribal-groupings (Hemiptera: Heteroptera) - Pluot-Sigwalt, Dominique; Moulet, Pierre (Zootaxa, 2020)
The morphology of the spermatheca is described in 109 species of 86 genera representing all four currently recognised subfamilies of Coreidae, covering the undivided Hydarinae, both tribes of Pseudophloeinae, all three tribes of Meropachyinae and 27 of the 32 tribes of Coreinae. Three types of spermatheca are recognised. Type I is bipartite, consisting only of a simple tube differentiated into distal seminal receptacle and proximal spermathecal duct and lacks the intermediate part present in most Pentatomomorpha, in which it serves as muscular pump. Type II is also bipartite but more elaborate in form with the receptacle generally distinctly wider than the duct. Type III is tripartite, with receptacle, duct and an often complex intermediate part. Four subtypes are recognised within type III. Type I is found only in Hydarinae and type II only in Pseudophloeinae. Type III is found in both Coreinae and Meropachyinae. Subtype IIIA (“Coreus-group”) unites many tribes from the Eastern Hemisphere and only one (Spartocerini) from the Western Hemisphere. Subtypes IIIB (“Nematopus-group”) and IIID (“Anisoscelis-group”) are confined to taxa from the Western Hemisphere and subtype IIIC (“Chariesterus-group”) is found in tribes from both hemispheres. The polarity of several characters of the intermediate part and some of the spermathecal duct is evaluated, suggesting autapomorphies or apomorphies potentially relevant to the classification of Coreidae at the sufamilial and tribal levels. Characters of the intermediate part strongly indicate that the separation of Meropachyinae and Coreinae as currently constituted cannot be substantiated. The tribes Anisoscelini, Colpurini, Daladerini and Hyselonotini are heterogeneous, each exhibiting two subtypes of spermatheca, and probably polyphyletic. Two tribes, Cloresmini and Colpurini, requiring further investigation remain unplaced. This study demonstrates the great importance of characters of the spermatheca, in particular its intermediate part, for research into the phylogeny and taxonomy of Pentatomomorpha.